Ekstraksi Tannin dari Daun Tanaman Putri Malu (Mimosa pudica) - Novi Pralisa Putri (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Putri malu(mimosa pudica) as a wild plant which has a tannin that useful to be a natural dye. To take the tannin from putri malu’s leaf, the extraction method with organic solvent can be used. The purpose of this research is to determine the initial concentration of putri malu. Before doing the extraction, the putri malu’s leaf must be dried first to reduce water in the leaf. Then, 5 mg putri malu’s leafis soaked in 350 mL ethanol 96% with variations of time and heated at constant temperature. After the extraction,analysis by spectrophotometry is used to get the tannin’s concentration dissolved in ethanol. After submersion, for 30 minutes the tannin’s concentration is 31,7 ppm, 60 minutes 31,9 ppm, 90 minutes 31,23 ppm, and 120 minutes 30,93 ppm. Based on the mathematic modeling, initially concentration is 32,1688 ppm.